2008
DOI: 10.1128/aem.00873-08
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Screening for Bleomycin Resistance Genes

Abstract: A metagenomic library of activated sludge was screened for bleomycin resistance genes. Two genes were identified that differed greatly from each other, from the genes of bleomycin-producing actinomycetes, and from those of clinical isolates. Therefore, the nonclinical environment is a rich reservoir of new resistance elements, and metagenomics can be used to sample the resistome rapidly.The antibiotic bleomycin (Bm) was first discovered in the culture broth of "Streptomyces verticillus" (14,17), an antitumor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 15 publications
0
34
0
1
Order By: Relevance
“…We showed that this BRP was functional and caused decreased susceptibility to bleomycin and bleomycin-like molecules, such as zeocin. Since Walsh et al demonstrated the large spread of the bla NDM-1 gene in bacteria recovered from environmental samples in New Delhi (32), it can be hypothesized that bleomycin or bleomycin-like molecules exert a selective pressure in the environment, in accordance with a metagenomic study that showed that BRP-encoding genes could be retrieved from activated sludge (14). In the United Kingdom and Germany, studies showed that bleomycin was present in sewage effluents, rivers, and potable water (1,29).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…We showed that this BRP was functional and caused decreased susceptibility to bleomycin and bleomycin-like molecules, such as zeocin. Since Walsh et al demonstrated the large spread of the bla NDM-1 gene in bacteria recovered from environmental samples in New Delhi (32), it can be hypothesized that bleomycin or bleomycin-like molecules exert a selective pressure in the environment, in accordance with a metagenomic study that showed that BRP-encoding genes could be retrieved from activated sludge (14). In the United Kingdom and Germany, studies showed that bleomycin was present in sewage effluents, rivers, and potable water (1,29).…”
Section: Resultsmentioning
confidence: 83%
“…In the case of Tn5, the bleomycin resistance gene is associated with a neomycin-kanamycin resistance gene (12). A recent metagenomic study revealed that the nonclinical environment might constitute a large reservoir of Bm resistance genes (14). Despite a high divergence between each other at the sequence level, those genes encode proteins conferring a similar resistance mechanism (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During the course of metagenomic library screening for various genes (Suenaga et al, 2007;Mori, Mizuta et al, 2008;, we constructed a metagenomic sequence database. In the search for various potentially useful enzymes, we identified a gene containing a copper-binding motif.…”
Section: Gene Cloning Overexpression and Protein Purificationmentioning
confidence: 99%
“…However, activity-based functional screening of metagenomic libraries, which provide direct evidence for antibiotic resistant phenotype, still remains a critical means to discover novel ARGs and identify their function that could be missed when using sequence based analysis only. Using functional screening of metagenomic libraries, novel functional ARGs have been identified from human microbiome (Sommer et al, 2009), organic pig gut (Kazimierczak et al, 2009), activated sludge (Mori et al, 2008) and soils (Allen et al, 2009;Lang et al, 2010;McGarvey et al, 2012). Most of these ARGs have not been identified previously and are evolutionarily distant from known resistance genes.…”
Section: Introductionmentioning
confidence: 99%